International Encyclopedia of the Social &Amp; Behavioral Sciences 2015
DOI: 10.1016/b978-0-08-097086-8.32164-x
|View full text |Cite
|
Sign up to set email alerts
|

Urban Sociology

Abstract: Space, place, and its connection to social relations make up the study of urban sociology. Urban sociology views cities as the spatial basis for the reproduction of inequality and as an integral part of the capitalist accumulation process. It relies on qualitative and quantitative methods to explain urban development, neighborhoods growth and decline, and their effects on people and their communities. Urban sociologists also rely more heavily on spatial methods to connect social relations to place. Contemporar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Segregation is a long-standing social phenomenon, broadly defined as the degree of spatial separation/isolation between two or more population groups, limiting their contacts, communications, and social relations ( Freeman, 1978 ; Newby, 1982 ). Since the early stage of modern cities was featured by separating different social, ethnic, and racial groups, this segregated social structure was preserved and still exists in today's society ( Shlay & Balzarini, 2015 ; Wong, 2016 ). Studies have demonstrated that segregation directly reflects and exacerbates social inequalities, which not only harms the socially vulnerable populations but also produces negative impacts on society as a whole ( Acs et al, 2017 ; Yao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Segregation is a long-standing social phenomenon, broadly defined as the degree of spatial separation/isolation between two or more population groups, limiting their contacts, communications, and social relations ( Freeman, 1978 ; Newby, 1982 ). Since the early stage of modern cities was featured by separating different social, ethnic, and racial groups, this segregated social structure was preserved and still exists in today's society ( Shlay & Balzarini, 2015 ; Wong, 2016 ). Studies have demonstrated that segregation directly reflects and exacerbates social inequalities, which not only harms the socially vulnerable populations but also produces negative impacts on society as a whole ( Acs et al, 2017 ; Yao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid and intense growth of the city, Chicago sociology observed the process of urbanization with wonder and awe. literally and figuratively anchors the entire field (Shlay & Balzarini, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Urban sociology was born out of the Chicago School, which embraced empirical research and its methods, including ethnography (Shlay and Balzarini 2015;Addams 1990Addams [1926). The discipline was also influenced by the work of Simmel (1950Simmel ( [1905), who drew attention to personal freedom as an essential element of what he termed the metropolitan individuality, a key characteristic of urban life and urban society.…”
Section: Introductionmentioning
confidence: 99%